The Influence Of E-Service Quality & E-Wom On Purchase Intention Of Ladyfame Shop Products - Gita Melani; Nabila Putri Maharani (SEAN Institute, 2024)
In this fast-growing modern world, more and more people are switching from offline shopping to online shopping. Indonesia is one of the countries with the largest e-commerce users. To sell its products online, fashion brand LadyFame Shop from Lampung uses e-commerce platforms such as Shopee. However, LadyFame Shop faces several challenges in running its business in e-commerce, such as keeping e-service quality high and managing e-WOM (electronic word of mouth) that affects consumer purchase intentions. These challenges are important to overcome for the business to thrive in the highly competitive online platform. In this context, this study investigates the influence of E-Service Quality and E-WOM on the purchase intention of Ladyfame Shop products through Shopee. The effect of E-Service Quality and E-WOM on customer purchase intention at LadyFame Shop was tested partially and simultaneously in this study. The method used is quantitative, data collected through surveys to 120 respondents who are LadyFame Shop consumers, and analyzed using statistical tests with SPSS software to measure the validity, reliability, significance and influence of each variable. The results showed that E-Service Quality has a positive and significant effect on purchase intention (t-count 2.943 > t table 0.179 or sig 0.004 < 0.005). while E-WOM has a positive and significant effect (t-count 8.410 > t table 0.179 or sig 0.000 < 0.005.). Simultaneously, both variables have a significant influence on consumer purchase intentions.